Fluorescência da clorofila e crescimento inicial de duas espécies de lianas, Cuspidaria sceptrum (Cham.) L.G. Lohmann e Fridericia florida (D.C) L.G. Lohmann, sob diferentes níveis de luminosidade - Paula, Sandro Mayrink (2014)
Among the factors which influence the development of the vegetation, light is one of the most important. When the light is scarce, the photosynthetic rates tend to decrease, and in excess, light may cause photoinhibition. In the semideciduos forests the light availability varies widely, changing continuously in time and space. This environment harbors plant species in the various levels of the ecological successional gradient, according their demand for light and acclimation capacity. The lianas are commonly found in the edges and gaps of these forests, which suggests they are heliophyte. However, little is known about the morphological and physiological responses of the lianas to changes in light intensity. In this context, the objective of this study was to assess the initial growth and the acclimation of two lianas species present in semideciduous forests of the Triângulo Mineiro, MG, Brazil, Fridericia florida and Cuspidaria sceptrum, at different levels of light. For this, several juvenile individuals were organized to form three treatments (full sun light, shade and forest edge) in the field of a semideciduous forest of the region. The plants were monitored for nine months in field, along which they had several morphological and physiological measurements periodically performed, such as number of leaves, height, diameter of the stem and dry mass of leaves, stem and roots. The potential quantum yield and electrons transport rates were measured using a pulse-amplitude modulated photosynthesis yield analyzer. At the same time, measurements about photosynthetic active radiation (400-700 nm) were recorded under full sun, shade and forest edge. At the end of the experiment, plants were harvested and the following parameters recorded: specific leaf area, leaf area ratio, leaf mass ratio, stem mass ratio and root/shoot ratio. The relative growth ratio was also calculated. Around the 180º day in field it was set up a new treatment for the two species in order to investigate the acclimation. Thus, half of the individuals growing under shade were transferred to sun light environment, where it remained until the end of the experiment. The results show that in general both species were able to survive and adapt to three light conditions, although they have exhibited low values of relative growth rates. It was found that two species have high morphophysiological plasticity, however, by distinct strategies, while C. sceptrum substitutes all of the leaves along the process when it was transferred from shade to full sun, F. florida keeps its. Besides, the tolerance to photoinhibition of the second species was a little higher due to smaller drops of the values of potential quantum yield observed in this species after transfer to full sun comparing with C. sceptrum. This scenery is compatible with the heterogeneous light regime of the semideciduous season forests.